The Adoption of Children with a Refugee Status: An Analysis of International Laws and Jurisprudence - Muhammad Nur; Galih Bagas Soesilo; Muhammad Rizal Sirojudin (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Objective: This research aims to undergo a juridical analysis of the stipulations for the adoption of refugee children from the perspective of international law. Methodology: This was juridical normative research that collected data using the literary study method. This research used primary legal materials, secondary legal materials, and non-legal materials research instruments. Findings: A core principle in making policies concerning refugee children is the ‘best interest rule’, which has two main implementations: the making of governmental policies and decisions made on the children as individuals. Adoption may only be considered after all efforts on tracing and reunifying child refugees with their families have failed, or if the child’s parents have agreed on that adoption according to the standard stipulated in the Convention on the Protection of Children and Co-operation in Respect of Intercountry Adoption. A jurisprudence concerning this was the case of Mariya Abdi Ibrahim vs Norway in the European Court of Human Rights for Application No. 15379/16. Indonesian stipulations are not in line with the international law that allows the adoption of refugee children. Application: This research may provide insight for the Indonesian government in considering an alternative care model for the many child refugees in Indonesia. Originality: This research described alternative model patterns that may be applied in Indonesia, as the government only regulated the prohibition of adopting international child refugees in Indonesia. But when referring to some international conventions, some types of alternative care are permitted, including adoption, even though it is only applied as a last resort. Keywords: adoption, children, refugee, international law, Indonesia.